CONTRIBUTION OF MUSIC FOR THE PREVENTION AND WELFARE OF THE EVILS CAUSED IN SOCIETY BY MENTAL DISTORTION: मानसिक विकृतियों द्वारा समाज में उत्पन्न कुरीतियों के निवारण एवं जनकल्याण हेतु संगीत का योगदान - Srivastava, Kinshuk (International Journal of Research -GRANTHAALAYAH, 2015)
The entire world is changing at a very fast pace since the transition phase of postmodernism. Science has, through various inventions, acquired complete dominance over the individual today. The use of Yantra in every sphere of life has made man himself a Yantra. All these changes have changed the way of life of human beings. Due to which mental distortions have taken place inside the person and evils have occurred in the society. Therefore, music is the only medium which is capable of destroying the evils generated in society. सम्पूर्ण विष्व आज उत्तर आधुनिकता के संक्रमणकाल के दौर से बड़ी तेज रफ्तार से बदल रहा है। विज्ञान ने आज विभिन्न अविष्कारों के माध्यम से व्यक्ति पर अपना पूर्णतः आधिपत्य जमा लिया है। जीवन के प्रत्येक क्षेत्र में यंत्र के प्रयोग ने मानव को स्वयं एक यंत्र बना दिया है। इन समस्त परिवर्तनों ने मानव की जीवन पद्धति को बदल दिया है। जिस कारण व्यक्ति के अंदर मानसिक विकृतियों ने जन्म लिया है और समाज मे कुरीतियाँ उत्पन्न हुई। अतः संगीत ही एक ऐसा माध्यम है जो समाज में उत्पन्न कुरीतियों को जड़ से नष्ट करने में सक्षम है।